00.06: Advances and development needs in the structural design of steel box girders for major bridges. (13th September 2017) - Polk, Henrik; Walker, Chris
ABSTRACT: Major cable‐supported bridges with a span exceeding 600m would not normally be feasible without a steel box girder to carry the traffic load. These box girders generally comprise a structural steel deck plate stiffened longitudinally by open or closed ribs and transversely by diaphragms. The stiffened deck plate supports the local wheel load and distributes it to the diaphragms from where it is transferred into the box girder. The stiffening ribs also increase the total cross‐sectional steel area and thereby contribute to the overall bending capacity of the box girder and finally, the stiffeners increase the resistance of the plate to buckling. This type of deck structure is generally called an "orthotropic bridge deck" due to the orthogonal nature of the stiffened deck plate and was first developed and utilised in 1950. The orthotropic steel deck is considerably lighter than a concrete slab in a composite girder and therefore makes longer span bridges possible, by reducing the self‐weight forces that would otherwise dominate. The self‐weight of the girder is a key driver in major bridge designs since it must be carried by all other bridge components, such as cables, towers, anchorages and foundations. The orthotropic steel girder is usually a fully closed box girder with all stiffening ribs placed inside the girder giving a smooth outer surface that is easy to paint and maintain. The interior of the closed box is often dehumidified without being painted giving an environmentally‐friendly fabrication that is safe to operate and maintain. However, the orthotropic steel deck is highly prone to fatigue meaning that the number of passing lorries, their axle/wheel configuration and total vehicle weight have a significant impact on the bridge deck design and fatigue life. The orthotropic deck therefore has higher fabrication costs when compared to conventional steel structures due to the high‐quality steel manufacturing and welding procedures that are necessary to achieve the required fatigue performance. The overall layout of an orthotropic bridge deck is basically unchanged since the 1960s, however the detailing has been refined considerably to a level where it is now seems difficult to improve it much further. However, the introduction of new materials e.g. sandwich steel deck structures in combination with new welding or gluing techniques could push box girder designs to new heights.